Photocatalytic composite material for decomposing automobile exhaust and preparation method thereof
By using titanium dioxide, diatomaceous earth and other components in photocatalytic materials, loading titanium dioxide on the surface of diatomaceous earth, the problem of poor durability and easy falling off when decomposing automobile exhaust is solved, and higher wear resistance and Decomposition efficiency.
Patent Information
- Application Number
- CN202411399284.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-11
AI Technical Summary
Existing photocatalytic materials have poor durability, are prone to fall off and are greatly affected by the environment when decomposing automobile exhaust.
Using photocatalytic composite materials including titanium dioxide, diatomaceous earth, gelatin, papain, turpentine and hydrochloric acid, the titanium dioxide is loaded on the surface of diatomaceous earth to enhance the compactness and frost resistance of the material through ultrasonic dispersion and low-temperature calcination. .
It significantly improves the wear resistance, erosion resistance and efficiency of decomposing automobile exhausts of photocatalytic composites, and solves the problems of poor durability and easy shedding.
Smart Images

Figure BDA0005074749970000091 
Figure BDA0005074749970000092 
Figure BDA0005074749970000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile exhaust decomposition, and in particular to a photocatalytic composite material for decomposing automobile exhaust and a preparation method thereof. Background Art
[0002] Gaseous pollutants have seriously affected the urban air environment and the health of residents. It is urgent to find a suitable technology to remove gaseous pollutants. The main pollutants in automobile exhaust include CO, hydrocarbons (HC), NOx, sulfides and particulate dust. Among them, NOx is a mixture of various nitrogen oxides. The harm of NOx is that it will cause major environmental problems such as photochemical smog, acid rain, greenhouse effect and ozone hole effect. At present, exhaust pollutants are generally removed by chemical or physical techniques. Commonly used techniques include physical adsorption and chemical oxidation. However, physical adsorption (activated carbon adsorption) will cause secondary pollution, and chemical oxidation methods are expensive. Photocatalytic technology is considered to be one of the effective methods to improve urban pollution. Photocatalysis refers to the process of converting light energy into chemical energy using photocatalysts and performing photocatalytic reactions.
[0003] Traditionally, nano titanium dioxide (TiO2) has been used to treat pollutants in industrial wastewater, domestic wastewater, and water treatment processes. In recent years, nano TiO2 has also been gradually used for the photocatalytic oxidation of atmospheric pollutants. At present, nano titanium dioxide is added to coatings and road surfaces, and the photocatalytic principle of nano titanium dioxide is used to purify automobile exhaust in tunnels, and certain results have been achieved. However, there are also many problems in the practical application of titanium dioxide. For example, the photocatalytic decomposition efficiency of nitrogen oxides is also related to light intensity and temperature and humidity. When titanium dioxide photocatalytic composite materials are paved on the road surface or used in coatings, the durability is low, and they are easy to fall off and the catalytic efficiency is seriously attenuated. Therefore, a new type of photocatalytic composite material is urgently needed for decomposing automobile exhaust. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a photocatalytic composite material for decomposing automobile exhaust and a preparation method thereof, so as to solve the problems that the current photocatalytic materials have poor durability, are easy to fall off, and are greatly affected by the environment when decomposing automobile exhaust.
[0005] The present invention solves the above problems through the following solutions:
[0006] A photocatalytic composite material for decomposing automobile exhaust gas, the photocatalytic composite material comprising the following raw materials:
[0007] Titanium dioxide, diatomaceous earth, gelatin, papain, turpentine, hydrochloric acid.
[0008] The photocatalytic composite material prepared by the present invention is mainly used for absorbing and decomposing automobile exhaust gas, and can be mixed in concrete for use, and can be made into coatings or paved roads. After titanium dioxide is directly mixed in concrete for use, titanium dioxide is not only easy to fall off but also has poor durability, and this effect is more obvious under freeze-thaw cycles. Therefore, in the process of preparing the photocatalytic composite material, the present invention selects diatomaceous earth and titanium dioxide to composite together to change the pore structure of concrete, so that the uniformity of the pore spacing is increased, the pore pressure in the freeze-thaw cycle is reduced, the compactness of the concrete is enhanced, and the antifreeze performance is improved. At the same time, because titanium dioxide is loaded on the surface of diatomaceous earth, it is avoided to agglomerate in the concrete, and the photocatalytic efficiency is fully exerted to achieve the purpose of decomposing automobile exhaust gas.
[0009] Furthermore, the mass ratio of the titanium dioxide to diatomaceous earth is 1:1, the mass ratio of the diatomaceous earth to gelatin is 1:(0.3-0.4), and the mass ratio of the gelatin to turpentine oil and papain is 1:(0.1-0.2):(0.02-0.05).
[0010] Furthermore, the titanium dioxide is anatase-type titanium dioxide nanoparticles, and the gelatin is type A gelatin.
[0011] Furthermore, the diatomite particle size is 325-350 mesh, and the specific surface area is 40-65m 2 / g, the particle size of the titanium dioxide is 10-20nm, and the specific surface area is 40-65m 2 / g.
[0012] Although titanium dioxide can be loaded on the surface of diatomaceous earth by ultrasonic dispersion, it is easy to fall off, especially after it is laid on the road, the wheels rub against it, which causes the falling speed to accelerate. Therefore, the present invention first washes the diatomaceous earth with hydrochloric acid solution to remove alkaline substances, so that the diatomaceous earth is more pure and the diatomaceous earth is placed in an acidic condition. The gelatin of the present invention uses type A gelatin prepared by acid method, and its isoelectric point is about 7-9. Therefore, after type A gelatin is made into a solution, the pH is adjusted to 7-9 so that it is around the isoelectric point, so that it has no charge or as little charge as possible. The surface of the diatomaceous earth in the acidic condition is protonated and positively charged. In the process of preparing the emulsion with turpentine and gelatin, the gelatin solution slowly deviates from the isoelectric point and becomes positively charged. This process causes the diatomaceous earth and gelatin to attract each other and adsorb more tightly. The emulsion is distributed on the surface and inside the pores of the diatomaceous earth. Titanium dioxide is then added and the pH is continuously adjusted to cause the gelatin to continue to deviate from the isoelectric point and carry more positive charges. Titanium dioxide will undergo hydrogen bonding in the emulsion to adsorb hydrogen ions and become protonated, making the surface positively charged. In this process, in addition to the van der Waals force, under the action of ultrasound, the titanium dioxide and the positively charged diatomaceous earth are further loaded more tightly and distributed more evenly through charge adsorption. Papain is then added to hydrolyze the gelatin to remove the connection between the gelatin and the diatomaceous earth, leaving only the titanium dioxide loaded on the diatomaceous earth. The pore structure of the diatomaceous earth is then adjusted to change slowly through low-temperature calcination with a slow temperature increase. While increasing the specific surface area, the internal structure of the space is changed to facilitate titanium dioxide to absorb ultraviolet light and decompose automobile exhaust.
[0013] The present invention also discloses a method for preparing a photocatalytic composite material for decomposing automobile exhaust gas, the preparation steps comprising:
[0014] (1) washing diatomaceous earth with a hydrochloric acid solution and drying it for standby use; preparing gelatin into a gelatin solution and adjusting the pH, adding turpentine oil and mixing evenly, then adding diatomaceous earth, and obtaining a gelatin diatomaceous earth emulsion after ultrasonic dispersion;
[0015] (2) adding titanium dioxide to gelatin diatomaceous earth emulsion and ultrasonically dispersing the emulsion, adjusting the pH with a hydrochloric acid solution, continuing ultrasonic dispersion and allowing to stand, adding papain for treatment after the standing is completed, then washing with an ethanol solution and calcining, taking out and cooling to room temperature after the calcination is completed, and obtaining a photocatalytic composite material.
[0016] Furthermore, in the step (1), the diatomaceous earth is washed with a 1 wt % hydrochloric acid solution, the concentration of the gelatin solution is 4-5 wt %, and the pH of the gelatin solution is adjusted to 7-9.
[0017] Furthermore, in the step (2), after ultrasonic dispersion for 5-10 minutes, the pH value is adjusted to 4-4.5 with a 5wt% hydrochloric acid solution, and ultrasonic dispersion is continued for 20-30 minutes and then allowed to stand for 2-4 hours.
[0018] Furthermore, after adding papain, the mixture is treated at 60-65° C. for 3-6 hours and then washed.
[0019] Furthermore, in the step (2), the temperature is increased to 300-450° C. at a heating rate of 20° C. / 10 min and then calcined for 10-20 min.
[0020] Beneficial effects:
[0021] The photocatalytic composite material prepared by the present invention can effectively decompose automobile exhaust gas, and the prepared photocatalytic composite material can be added to concrete for paving roads or applied to paint on building surfaces. After addition and use, its wear resistance and erosion resistance are significantly improved, which can effectively solve the problems of poor durability, easy shedding, and greater environmental impact. DETAILED DESCRIPTION
[0022] The present invention will be described in detail below with reference to specific embodiments:
[0023] Unless otherwise specified, the experimental methods used in the examples of the present invention are all conventional methods. The materials, reagents, etc. used in the examples of the present invention, unless otherwise specified, can be obtained from commercial channels.
[0024] Example 1: Preparation of photocatalytic composite materials
[0025] Weigh the following raw materials:
[0026] 100g titanium dioxide, 100g diatomaceous earth, 30g type A gelatin, 0.6g papain, 3g turpentine, hydrochloric acid is made into 1wt% and 5wt% hydrochloric acid solutions, wherein the diatomaceous earth is selected with a particle size of 325-350 mesh and a specific surface area of 40-65m 2 / g, fine-pored diatomite with SiO2 content ≥85%, the particle size of titanium anatase type titanium dioxide is 10-20nm, and the specific surface area is 40~65m 2 / g, purity ≥98%, the specific preparation process is as follows:
[0027] (1) Washing diatomaceous earth with a 1 wt % hydrochloric acid solution and drying it with hot air at 70° C. for standby use; mixing gelatin with water and heating it to prepare a 4 wt % gelatin solution, then adjusting the pH to 8, adding turpentine oil and mixing well, and then adding diatomaceous earth, dispersing under ultrasonic conditions of an ultrasonic power of 450 W and an ultrasonic treatment time of 10 min to obtain a gelatin diatomaceous earth emulsion; during the emulsification process, an appropriate amount of 1 wt % Tween-80 of gelatin can be added;
[0028] (2) Add titanium dioxide to gelatin diatomaceous earth emulsion and continue ultrasonic dispersion for 5 minutes, then adjust the pH to 4 with a 5wt% hydrochloric acid solution, continue ultrasonic dispersion for 20 minutes and let it stand for 2 hours. After standing, add papain, heat to 60°C for 3 hours, wash with 70% ethanol solution, and then heat to 300°C at a heating rate of 20°C / 10min for calcination. After calcination for 10 minutes, cool to room temperature to obtain a photocatalytic composite material.
[0029] Example 2: Preparation of photocatalytic composite materials
[0030] Weigh the following raw materials:
[0031] 150g titanium dioxide, 150g diatomaceous earth, 60g gelatin, 3g papain, 12g turpentine, hydrochloric acid is made into 1wt% and 5wt% hydrochloric acid solutions, and the specific preparation process is as follows:
[0032] (1) Washing diatomaceous earth with 1 wt% hydrochloric acid solution and drying with hot air at 70°C for standby use; mixing gelatin and water and heating them to prepare a 5 wt% gelatin solution, then adjusting the pH to 7, adding turpentine oil and mixing well, and then adding diatomaceous earth, dispersing under ultrasonic conditions of 450 W ultrasonic power and 15 min ultrasonic treatment time to obtain a gelatin diatomaceous earth emulsion; during the emulsification process, an appropriate amount of 1% Tween-80 by weight of gelatin can be added;
[0033] (2) Add titanium dioxide to gelatin diatomaceous earth emulsion and continue ultrasonic dispersion for 10 minutes, then adjust the pH to 4.5 with a 5wt% hydrochloric acid solution, continue ultrasonic dispersion for 30 minutes and let it stand for 4 hours. After standing, add papain, heat to 65°C for 6 hours, wash with 70% ethanol solution, and then heat to 450°C at a heating rate of 20°C / 10min for calcination. After calcination for 10 minutes, cool to room temperature to obtain a photocatalytic composite material.
[0034] Example 3: Preparation of photocatalytic composite materials
[0035] Weigh the following raw materials:
[0036] 130g titanium dioxide, 130g diatomaceous earth, 50g gelatin, 1.5g papain, 7.5g turpentine, hydrochloric acid is made into 1wt% and 5wt% hydrochloric acid solutions, and the specific preparation process is as follows:
[0037] (1) Washing diatomaceous earth with 1 wt% hydrochloric acid solution and drying with hot air at 70°C for standby use; mixing gelatin and water and heating them to prepare a 5 wt% gelatin solution, then adjusting the pH to 9, adding turpentine oil and mixing well, and then adding diatomaceous earth, dispersing under ultrasonic conditions of 450 W ultrasonic power and 13 min ultrasonic treatment time to obtain a gelatin diatomaceous earth emulsion; during the emulsification process, an appropriate amount of 1% Tween-80 by weight of gelatin can be added;
[0038] (2) Add titanium dioxide to gelatin diatomaceous earth emulsion and continue ultrasonic dispersion for 8 minutes, then adjust the pH to 4 with a 5wt% hydrochloric acid solution, continue ultrasonic dispersion for 25 minutes and let stand for 3 hours. After standing, add papain, heat to 65°C for 3 hours, wash with 70% (v / v) ethanol solution, and then heat to 400°C at a heating rate of 20°C / 10min for calcination. After calcination for 15 minutes, cool to room temperature to obtain a photocatalytic composite material.
[0039] Comparative Example 1:
[0040] This comparative example is in contrast to Example 1, the difference being that this comparative example only uses ultrasonic dispersion to load titanium dioxide on diatomaceous earth. The specific preparation method is as follows:
[0041] 100 g of diatomaceous earth and titanium dioxide were weighed respectively and mixed to obtain composite powder. 40 g of nano-dispersant was made into a 4% aqueous solution and added to the composite powder. Ultrasonic power was 450 W. Ultrasonic treatment time was 30 min. Then the product was taken out and dried with hot air to obtain a photocatalytic composite material.
[0042] Comparative Example 2:
[0043] This comparative example is compared with Example 1, the difference being that the diatomaceous earth in step (1) of this comparative example is not cleaned with a hydrochloric acid solution, and the subsequent operations are the same.
[0044] Comparative Example 3:
[0045] This comparative example is in contrast to Example 1, the difference being that in step (1) of this comparative example, no emulsion preparation is performed, and the gelatin solution and diatomaceous earth are directly ultrasonically dispersed. The specific operation is as follows:
[0046] (1) Clean diatomaceous earth with 1 wt % hydrochloric acid solution and dry it with hot air at 70° C. for standby use; mix gelatin and water and heat them to prepare a 5 wt % gelatin solution, then adjust the pH to 8, add diatomaceous earth, and disperse under ultrasonic conditions of 450 W ultrasonic power and 10 min ultrasonic treatment time to obtain a gelatin-diatomaceous earth mixed colloid; the subsequent operations are the same.
[0047] Comparative Example 4:
[0048] This comparative example is in contrast to Example 1, the difference being that the pH is not adjusted in step (1) of this comparative example, and the specific operation is as follows:
[0049] (1) Wash diatomaceous earth with 1 wt % hydrochloric acid solution and dry it with hot air at 70° C. for standby use; mix gelatin and water and heat them to make a 4 wt % gelatin solution, add turpentine oil and mix well, then add diatomaceous earth, and disperse under ultrasonic conditions of 450 W ultrasonic power and 10 min ultrasonic treatment time to obtain a gelatin diatomaceous earth emulsion; during the emulsification process, an appropriate amount of 1 wt % Tween-80 of gelatin can be added; the subsequent operations are the same.
[0050] Comparative Example 5:
[0051] This comparative example is in contrast to Example 1, the difference being that the pH is not adjusted in step (2) of this comparative example. The specific operation is as follows:
[0052] (1) Washing diatomaceous earth with a 1 wt % hydrochloric acid solution and drying it with hot air at 70° C. for standby use; mixing gelatin with water and heating it to prepare a 4 wt % gelatin solution, then adjusting the pH to 8, adding turpentine oil and mixing well, and then adding diatomaceous earth, dispersing under ultrasonic conditions of an ultrasonic power of 450 W and an ultrasonic treatment time of 10 min to obtain a gelatin diatomaceous earth emulsion; during the emulsification process, an appropriate amount of 1 wt % Tween-80 of gelatin can be added;
[0053] (2) Titanium dioxide was added to the gelatin diatomaceous earth emulsion and ultrasonic dispersion was continued for 25 minutes, and then it was allowed to stand for 2 hours. After standing, papain was added, and then it was heated to 60°C for 3 hours, and then washed with 70% ethanol solution, and then heated to 300°C at a heating rate of 20°C / 10min for calcination. After calcination for 10 minutes, it was cooled to room temperature to obtain a photocatalytic composite material.
[0054] Comparative Example 6:
[0055] This comparative example is in contrast to Example 1, the difference being that papain is not added in step (2) of this comparative example, and the specific operation is as follows:
[0056] (1) Washing diatomaceous earth with a 1 wt % hydrochloric acid solution and drying it with hot air at 70° C. for standby use; mixing gelatin with water and heating it to prepare a 4 wt % gelatin solution, then adjusting the pH to 8, adding turpentine oil and mixing well, and then adding diatomaceous earth, dispersing under ultrasonic conditions of an ultrasonic power of 450 W and an ultrasonic treatment time of 10 min to obtain a gelatin diatomaceous earth emulsion; during the emulsification process, an appropriate amount of 1 wt % Tween-80 of gelatin can be added;
[0057] (2) Add titanium dioxide to gelatin diatomaceous earth emulsion and continue ultrasonic dispersion for 5 minutes, then adjust the pH to 4 with a 5wt% hydrochloric acid solution, continue ultrasonic dispersion for 20 minutes, let it stand for 2 hours, then wash it with a 70% ethanol solution, and then heat it to 300°C at a heating rate of 20°C / 10min for calcination. After calcination for 10 minutes, cool it to room temperature to obtain a photocatalytic composite material.
[0058] Comparative Example 7:
[0059] This comparative example is compared with Example 1, the difference being that in step (2), the comparative example is directly placed in a preheated 300° C. furnace for calcination.
[0060] Comparative Example 8:
[0061] This comparative example is compared with Example 1, the difference being that in this comparative example, no calcination is performed in step (2), and hot air drying is performed directly after ethanol washing.
[0062] Comparative Example 9:
[0063] This comparative example is compared with Example 1, and the difference is that in this comparative example, ethanol is used for washing in step (2), while clean water is directly used for washing and then heating and calcining.
[0064] Comparative Example 10:
[0065] This comparative example is in contrast to Example 1, the difference being that in step (1) of this comparative example, type B gelatin is used. The specific preparation method is as follows:
[0066] (1) washing diatomaceous earth with a 1 wt % hydrochloric acid solution and drying it with hot air at 70° C. for standby use; mixing gelatin and water and heating them to prepare a 4 wt % gelatin solution, then adjusting the pH to 5, adding turpentine oil and mixing well, then adding diatomaceous earth, and dispersing under ultrasonic conditions of an ultrasonic power of 450 W and an ultrasonic treatment time of 10 min to obtain a gelatin diatomaceous earth emulsion;
[0067] (2) Add titanium dioxide to gelatin diatomaceous earth emulsion and continue ultrasonic dispersion for 5 minutes, then adjust the pH to 2 with a 5wt% hydrochloric acid solution, continue ultrasonic dispersion for 20 minutes and let it stand for 2 hours. After standing, add papain, heat to 60°C for 3 hours, wash with 70% ethanol solution, and then heat to 300°C at a heating rate of 20°C / 10min for calcination. After calcination for 10 minutes, cool to room temperature to obtain a photocatalytic composite material.
[0068] Comparative Example 11:
[0069] This comparative example is in contrast to Example 1, the difference being that the material of the present invention is pure titanium dioxide.
[0070] The photocatalytic composite material prepared above was used for automobile exhaust decomposition experiment.
[0071] Experiment 1:
[0072] 1. Light source selection: Two 80W and one 60W UVA fluorescent lamps are used as the light source of the test system. The internal temperature of the sealed box is controlled at room temperature 25℃.
[0073] 2. Spread 100g of the composite photocatalytic material evenly on a tile with a size of 30cm×25cm, and place it in a reaction chamber (the size of the gas reaction chamber is 450mm×400mm×300mm (length×width×height), the thickness of the plexiglass is 10mm, and the volume of the reaction chamber is about 50L. An air inlet valve is set in the middle position of the side and connected to a rotor flowmeter to control the inflation speed; an exhaust valve is set and connected to an exhaust gas analyzer to extract the reaction chamber gas for detection, and then the extracted exhaust gas is recovered to the reaction chamber through the recovery port to eliminate the effect of exhaust on the gas concentration in the reaction chamber), and the standard gas is introduced at a rate of 3L / min for 2min. The initial exhaust gas concentration in the sealed box is shown in Table 1; after the ventilation is completed, the air inlet valve is closed, the ultraviolet lamp and the exhaust gas analyzer are turned on, and the change in exhaust gas concentration in the reaction chamber is tested. The final results are shown in Table 2. Comparative Example 11 is titanium dioxide nanopowder.
[0074] Table 1
[0075]
[0076] Table 2
[0077]
[0078] Experiment 2:
[0079] The wear resistance of concrete was tested by using a ball bearing wear tester. After starting the machine, the machine was pre-grinded for 30 revolutions, and the initial grinding groove depth was measured and recorded as P0. Then the grinding groove depth was measured every 1000 revolutions. When the number of revolutions of the grinding head reached 4000 revolutions, the test ended. The grinding groove depth was measured using a vernier caliper, and the average value was taken as the grinding groove depth P. f , accurate to 0.01mm. Final grinding groove depth P = P f -P0, measure and record the number of grinding head revolutions and the final grinding groove depth for many times. Wear resistance Is = √R / P, where Is is the wear resistance, R is the grinding head speed (unit / thousand revolutions), and P is the grinding groove depth difference (unit / mm).
[0080] The mass ratio of concrete is as follows: cement, sand, stone, water, water reducing agent, photocatalytic composite material = 1:1.8:3.5:0.43:0.009:0.2, where the cement is PO 42.5 ordinary Portland cement with a density of 3050Kg / m 3 The water reducing agent is polycarboxylic acid water reducing agent (water reducing rate 25%), the coarse aggregate is 5-19mm river pebble gravel, and the apparent density is 2960Kg / m 3 , compact bulk density 1780Kg / m 3 The fine aggregate is medium sand manufactured from zone II, and the fineness modulus is 3.0.
[0081] The above concrete was made into a 10cm×10cm×5cm mold to make a test piece. The test mold was filled with mortar at one time, and a tamping rod was used to evenly tamp 25 times from the outside to the inside in a spiral direction. In order to prevent the low-consistency mortar from leaving holes after tamping, a putty knife was allowed to be inserted along the mold wall several times. The test piece was made in an environment with a temperature of 20℃±5℃ and a humidity greater than 50%. It was left for a day and night (24h±2h) and then the test piece was demolded. It should continue to be cured for 7 days under standard curing conditions (temperature 20℃±2℃, relative humidity ≥90%). The blank group is a concrete test piece without adding photocatalytic composite materials. The obtained data are shown in Table 3:
[0082] Table 3
[0083]
[0084] Experiment 3:
[0085] The prepared photocatalytic composite material is made into a building coating for use. The concrete substrate is from bottom to top: concrete base, epoxy resin primer (Nippon primer), putty (Nippon exterior wall leveling putty, brushing thickness 0.5mm), photocatalytic composite latex topcoat (photocatalytic composite material and exterior wall latex paint mass ratio 1:10), wherein the blank control does not add photocatalytic composite material to the topcoat, the preparation of the concrete substrate refers to experiment 2, the mass ratio is as follows, cement, sand, stone, water, water reducer = 1:1.8:3.5:0.43:0.009, the primer and topcoat are brushed evenly in one layer. The above coating is subjected to a wash resistance test, the test method refers to GB / T9266, and the results are shown in Table 4:
[0086] Table 4
[0087] Washability (times) Washability (times) Example 1 4133 Comparative Example 6 2390 Comparative Example 1 3799 Comparative Example 7 3046 Comparative Example 2 4039 Comparative Example 8 2915 Comparative Example 3 3564 Comparative Example 9 3604 Comparative Example 4 3281 Comparative Example 10 3893 Comparative Example 5 3356 Comparative Example 11 3540 Blank control 3285
[0088] Result analysis:
[0089] 1. The photocatalytic composite material prepared by the present invention can be used to decompose automobile exhaust. The CO decomposition rate of Example 1 reached 79.2%, the CH decomposition rate reached 61.1%, and the NO decomposition rate reached 82.1%, and the wear resistance and washability were good, indicating that the photocatalytic composite material prepared by the present invention can not only be used for automobile exhaust decomposition, but also has high wear resistance and washability after mixing with concrete, and has high adhesion.
[0090] 2. The effects of Comparative Examples 1 and 11 are poorer than those of Example 1, mainly because the titanium dioxide is easily detached when titanium dioxide is attached to diatomaceous earth only by ultrasound, or it is difficult for titanium dioxide powder to synergistically adsorb and decompose automobile exhaust with diatomaceous earth directly. At the same time, because diatomaceous earth loaded with titanium dioxide can improve the interface structure of coatings or concrete, it can significantly improve the wear resistance and erosion resistance. Therefore, the effects of Comparative Examples 1 and 11 are poor.
[0091] 3. Comparative Examples 3 to Comparative Examples 9 mainly differ in the preparation steps of the photocatalytic composite materials. Comparative Example 3 directly uses gelatin in a sol state for treatment, Comparative Example 6 does not perform a gelatin hydrolysis process, and Comparative Example 9 does not perform ethanol cleaning. Due to the high viscosity of the sol, it is very easy to cause titanium dioxide and diatomaceous earth to agglomerate when loaded, resulting in a decrease in loading efficiency. Therefore, the present invention selects gelatin to be made into an emulsion and distributed on the surface and inside the pores of diatomaceous earth, combined with adjusting the pH to promote the loading of titanium dioxide and diatomaceous earth. Failure to hydrolyze the gelatin will cause the gelatin to adhere to the surface of the photocatalytic composite material during the calcination process. Although the wear resistance is improved, the gas degradation rate and the flushing resistance will be significantly reduced. Finally, ethanol cleaning is used to remove turpentine and hydrolyzed gelatin as much as possible to avoid the impact during the calcination process. Comparative Examples 2, 4 and 5 are mainly about adjusting the pH of the preparation process. During this treatment process, diatomaceous earth and type A gelatin adsorb each other and present a positive charge. After further deviating from the isoelectric point, there are more positive charges in the solution, which promotes the use of gelatin as a connection to compound more titanium dioxide and diatomaceous earth together, and the diatomaceous earth can also be acid-washed to remove impurities. The raw material used in Comparative Example 10 is type B gelatin. Type B gelatin has a higher viscosity and a lower isoelectric pH due to alkali treatment, which makes it more complicated to operate with a positive charge. Under over-acidic conditions, the effect of diatomaceous earth and titanium dioxide loading is worse, and the gas degradation rate is lower.
[0092] 4. Comparative Examples 7 and 8 have different calcination operations during the preparation process. Calcination can not only adjust the pore structure of diatomaceous earth but also completely remove substances such as gelatin and turpentine during the loading process. However, if the temperature changes too quickly during direct high-temperature calcination, it is very easy to cause the combustion residues to adhere to the surface of the diatomaceous earth, reduce the contact area between the exhaust gas and titanium dioxide, and reduce the decomposition rate.
[0093] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.
Claims
1. A photocatalytic composite material for decomposing automobile exhaust, characterized in that: The photocatalytic composite material comprises the following raw materials: Titanium dioxide, diatomaceous earth, gelatin, papain, turpentine, hydrochloric acid.
2. The photocatalytic composite material for decomposing automobile exhaust according to claim 1, characterized in that: The mass ratio of the titanium dioxide to diatomaceous earth is 1:1, the mass ratio of the diatomaceous earth to gelatin is 1:(0.3-0.4), and the mass ratio of the gelatin to turpentine oil and papain is 1:(0.1-0.2):(0.02-0.05).
3. The photocatalytic composite material for decomposing automobile exhaust according to claim 2, characterized in that: The titanium dioxide is anatase-type titanium dioxide nanoparticles, and the gelatin is type A gelatin.
4. The photocatalytic composite material for decomposing automobile exhaust according to claim 3, characterized in that: The diatomite particle size is 325-350 mesh, and the specific surface area is 40-65m 2 / g, the particle size of the titanium dioxide is 10-20nm, and the specific surface area is 40-65m 2 / g.
5. A method for preparing a photocatalytic composite material for decomposing automobile exhaust according to any one of claims 1 to 4, characterized in that: The preparation steps include: (1) washing diatomaceous earth with a hydrochloric acid solution and drying it for standby use; preparing gelatin into a gelatin solution and adjusting the pH, adding turpentine oil and mixing evenly, then adding diatomaceous earth, and obtaining a gelatin diatomaceous earth emulsion after ultrasonic dispersion; (2) adding titanium dioxide to gelatin diatomaceous earth emulsion and ultrasonically dispersing the emulsion, adjusting the pH with a hydrochloric acid solution, continuing ultrasonic dispersion and allowing to stand, adding papain for treatment after the standing is completed, then washing with an ethanol solution and calcining, taking out and cooling to room temperature after the calcination is completed, and obtaining a photocatalytic composite material.
6. The method for preparing a photocatalytic composite material for decomposing automobile exhaust according to claim 5, characterized in that: In the step (1), the diatomaceous earth is washed with a 1 wt % hydrochloric acid solution, the concentration of the gelatin solution is 4-5 wt %, and the pH of the gelatin solution is adjusted to 7-9.
7. The method for preparing a photocatalytic composite material for decomposing automobile exhaust according to claim 6, characterized in that: In the step (2), after ultrasonic dispersion for 5-10 minutes, the pH is adjusted to 4-4.5 with a 5wt% hydrochloric acid solution, and ultrasonic dispersion is continued for 20-30 minutes, followed by standing for 2-4 hours.
8. The method for preparing a photocatalytic composite material for decomposing automobile exhaust according to claim 7, characterized in that: After adding papain, treat at 60-65℃ for 3-6h and then wash.
9. The method for preparing a photocatalytic composite material for decomposing automobile exhaust gas according to claim 8, characterized in that: In the step (2), the temperature is increased to 300-450° C. at a heating rate of 20° C. / 10 min and then calcined for 10-20 min.
10. The method for preparing a photocatalytic composite material for decomposing automobile exhaust gas according to claim 9, characterized in that: The prepared photocatalytic composite material is used for decomposing automobile exhaust gas.